A study of criteria of healing garden for elderly in reducing their stress - 309396 Chin, Siew Moy; Hasanuddin Lamit, supervisor; Fakulti Alam Bina (2006)
Topical Study (Sarjana Muda (Senibina Landskap)) - Universiti Teknologi Malaysia, 2006